Մեկ հերոսի կենտրոնացումը Հ. Խաչատրյանի «Արտավազդ» պատմավեպում - Բեգլարյան, Ժ.
В статье автор выдвигает значимость исторического романа А. Хачатряна «Артавазд» в ряду его исторических романов. Убедительным литературоведческим анализом роман оценивается с литературно-художественной, эстетической и познавательной позиции. К образу Артавазда писатель обращается в «Тигране Великом», далее образ Арташесидского властителя развертывается во второй книге «Артавазд», где царь царей Артавазд представлен трагическим персонажем. Это освоение нового качества в общей системе персонажей писателя. The article is devoted to the place of H. Khachatryan’s "Artavazd" novel in a series of his historical novels. By means of convincing literary analysis the novel is evaluated from the artistic, aesthetic and cognitive position. The author turns to the figure of Artavazd in"Tigran the Great", then developes the figure of the Artashesyan ruler in the second book "Artavazd", in which the king of the kings is introduced as a tragical personage. This is a mastering of a new quality in the common system of the author’s personages.
Keywords: Գրականագիտություն